2001
DOI: 10.1097/00004032-200111000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Correction Factors in the Epr Dose Reconstruction for Residents of the Middle and Lower Techa Riverside

Abstract: During 1949-1956, the first Soviet nuclear weapons plant, Mayak, released about 7.6 x 10(7) m(-3) of liquid radioactive waste with a total activity of 10(17) Bq into the Techa River (Southern Urals, Russia). 90Sr contributed 11.6% to the total waste radioactivity. As a result of these radioactive discharges, about 28,000 local residents were exposed to ionizing radiation, and some of them received relatively high doses. Internal exposure of the population residing at the Middle and Lower Techa riverside was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Gy in the teeth that had already been completed at that time (Tolstykh et al, 2000;Romanyukha et al, 2001). Because of the differences in the development processes of teeth in different buccal positions, incorporation of radioisotopes into teeth of different types occurs at different ages.…”
Section: Epr Response Of Tooth Enamel To Doses From Internal β β β β-mentioning
confidence: 99%
See 2 more Smart Citations
“…Gy in the teeth that had already been completed at that time (Tolstykh et al, 2000;Romanyukha et al, 2001). Because of the differences in the development processes of teeth in different buccal positions, incorporation of radioisotopes into teeth of different types occurs at different ages.…”
Section: Epr Response Of Tooth Enamel To Doses From Internal β β β β-mentioning
confidence: 99%
“…Dentine was used for dose reconstructions in a small number of studies (Goksu et al, 2002;Romanyukha et al, 2001). …”
Section: Epr Dosimetry Using Dentinementioning
confidence: 99%
See 1 more Smart Citation
“…However, EPR dosimetry remains a very sensitive technique for retrospective dosimetry and epidemiological studies [11,[62][63][64][65][66][67][68] with recent advancements that allows in vivo measurements [69].…”
Section: Epr Dosimetrymentioning
confidence: 99%
“…These other dose contributions have to be estimated by independent methods, e.g., the natural background exposure can be evaluated by the dose rate in the region of residence and the tooth age and medical or occupational radiation exposures may be estimated by an interview of the tooth donor about his/her radiation history. If it is known that bone seeking radionuclides like 90 Sr were incorporated in teeth tissues to a significant extent, an independent measurement of the concentration of 90 Sr in teeth needs to be carried out in order to determine the relative contributions from external exposures and internal contamination (Romanyukha et al, 2001;Veronese et al, 2006). Göksu et al (2002a, b) and Shishkina et al (2005) have shown that the 90 Sr concentration in dental tissue can be measured using passive beta detectors; a good correlation with the measured EPR values was obtained in their experiments.…”
Section: Electron Paramagnetic Resonancementioning
confidence: 99%